Hybrid biocomposites from polypropylene, sustainable biocarbon and graphene nanoplatelets - Watt, Ethan; Abdelwahab, Mohamed A.; Snowdon, Michael R.; Mohanty, Amar K.; Khalil, Hamdy; Misra, Manjusri (Scientific reports, 2020)
Polypropylene (PP) is an attractive polymer for use in automotive parts due to its ease of processing, hydrophobic nature, chemical resistance and low density. The global shift towards eliminating non-renewable resource consumption has promoted research of sustainable biocarbon (BioC) filler in a PP matrix, but this material often leads to reduction in composite strength and requires additional fillers. Graphene nano-platelets (GnPs) have been the subject of considerable research as a nanofiller due to their strength, while maleic anhydride grafted polypropylene (MA-g-PP) is a commonly used compatibilizer for improvement of interfacial adhesion in composites. This study compared the thermo-mechanical properties of PP/BioC/MA-g-PP/GnP composites with varying wt.% of GnP. Morphological analysis revealed uniform dispersion of BioC, while significant agglomeration of GnPs limited their even dispersion throughout the PP matrix. In the optimal blend of 3 wt.% GnP and 17 wt.% BioC biocontent, tensile strength and modulus increased by ~19% and ~22% respectively, as compared to 20 wt.% BioC biocomposites. Thermal stability and performance enhancement occurred through incorporation of the fillers. Thus, hybridization of fillers in the compatibilized matrix presents a promising route to the enhancement of material properties, while reducing petroleum-based products through use of sustainable BioC filler in composite structures.